THE ASSOCIATION BETWEEN ATRIAL FIBRILLATION AND CENTRAL RETINAL ARTERY OCCLUSION: A META-ANALYSIS AND SYSTEMATIC REVIEW: Oral Presentation - Observational Study - General practitioner - Amelia, Yufilia Suci; Alberta, Ivana Beatrice; Angelia, Maria; Pratama, Kevin Gracia (Majalah Oftalmologi Indonesia, 2023)
Introduction Central retinal artery occlusion (CRAO) is a condition where the central retinal artery is blocked. Atrial Fibrillation (AF) is commonly associated with retinal embolism that originates anywhere between the heart and the ophthalmic artery. This study aims to explore the incidence of AF in CRAO. Methods A systematic search was performed in three databases: Pubmed, EBSCO host, and Proquest. Newcastle-Ottawa Scale was used to assess the risk of bias in the study included. Results Our systematic review comprises six studies, 4 studies included CRAO patients as the study population and AF as the endpoint, and the other 2 studies with CRAO as the endpoint. Meta-analysis of the first group resulted in a significantly favorable AF incident after CRAO with an odds ratio (OR) of 1.46 (95% CI 1.17-1.81, p=0.0007). The second metaanalysis supports CRAO with an OR of 4.86 (95% CI 2.30-10.28, p<0.0001). Discussion Our study indicates that AF is a significant risk factor for CRAO. Extended cardiac monitoring may play a crucial diagnostic role in CRAO patients, and longer-term monitoring (23 years) may be a reasonable option as part of the diagnostic workup. Short-term monitoring alone may fail to detect a significant proportion of patients with underlying AF. Conclusions It is crucial to identify AF in preventing ocular infarction. This study revealed that AF was identified as a risk factor in patients with CRAO and vice versa.